পরিবেশ : রাজনৈতিক দলের ভূমিকা - ফারূক, মোহিউদ্দিন; আহমদ, মেসবাহ; কবির, ইকবাল; বাংলাদেশ পরিবেশ আইনবিদ সমিতি (বেলা) (ঢাকা : বাংলাদেশ পরিবেশ আইনবিদ সমিতি (বেলা), 1995)
On environment in Bangladesh and role of political parties; papers read at a opinion meeting organized by Bāṃlādeśa Paribeśa Āinabida Samiti, Dhaka.
In Bengali.
Keywords: Ecology -- Bangladesh -- Congresses; Ecology -- Political aspects -- Bangladesh -- Congresses